2022
DOI: 10.33225/pec/22.80.426
|View full text |Cite
|
Sign up to set email alerts
|

Academic Misconduct: Attitudes and Perceptions of Brazilian Medical Students

Abstract: Academic misconduct during medical school is common, with multifactorial causes, and can negatively impact the training and professional performance of future physicians. This study investigated factors linked to academic misconducts among medical students during their training. It is a transversal, quantitative, and analytical study that assessed the perception of 240 students from five medical courses in Salvador, Bahia, Brazil. A virtual, semi-structured, anonymous, self-completed questionnaire was used, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Farahat’s study indicated laziness and lack of knowledge about academic integrity were the major antecedents for misconduct besides parents’ pressure to earn high grades. 16 Regarding attributes, Dorea-Bandeira et al 15 and Farahat 16 indicated that unethical behavior and violation of academic integrity are common characteristics of misconduct. Both studies concluded that misconduct leads to the loss of credibility of the graduates and leaves students confused regarding the sense of professional ethics.…”
Section: Design and Search Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Farahat’s study indicated laziness and lack of knowledge about academic integrity were the major antecedents for misconduct besides parents’ pressure to earn high grades. 16 Regarding attributes, Dorea-Bandeira et al 15 and Farahat 16 indicated that unethical behavior and violation of academic integrity are common characteristics of misconduct. Both studies concluded that misconduct leads to the loss of credibility of the graduates and leaves students confused regarding the sense of professional ethics.…”
Section: Design and Search Methodsmentioning
confidence: 99%
“…Both studies concluded that misconduct leads to the loss of credibility of the graduates and leaves students confused regarding the sense of professional ethics. 15,16…”
Section: Design and Search Methodsmentioning
confidence: 99%
See 3 more Smart Citations